Like Mother, Like Father? Gender Assortative Transmission of Child Overweight - Joan Costa-i-Font; Mireia Jofre-Bonet (Center for Economic Studies and ifo Institute (CESifo), 2016)
Parental influences on children health related behaviours are argued to be gender assortative (e.g., that maternal behaviour is more important for daughters), but research devoted to disentangling such effects is still at its infancy. We take advantage of a unique dataset (Health Survey for England) containing records of clinically measured weight and height for a representative sample of English children and their parents for the period 1996-2009. We examine the magnitude and change of the association between maternal and paternal overweight and that of their offspring by gender, alongside the combined parental effect. We aim at identifying the existence and the magnitude of a gender-assortative transmission of overweight after controlling for a long list of covariates, including time and survey-wave fixed effects. Our findings point out that the intergenerational transmission is most significant when both parents are obese or overweight, and the effects size increases with child age 0.7 percentage point among infants to 1.3-1.4 percentage points among schooled children and teenagers. However, we find weak evidence of a specific maternal effect on girls' overweight, and more generally gender assortative intergenerational transmission of overweight and obesity.
Keywords: I12; 330; gender assortative parental transmission; child obesity; child overweight; role models; inter-generational transmission